Blockchain Technology: Applications, Benefits and Challenges - Baygin, Nursena; Baygin, Mehmet; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2019)
Blockchain is the name given to the technology that allows any data set to be stored in a distributed manner. It provides a secure structure with its distributed structure and provides a transparent system with the data set easily accessible by each user. Bitcoin application using blockchain infrastructure has gained attention with its reliability, robustness and performance. Thus, the blockchain is provided to reach large masses. Although the blockchain stands out as the technology of the future, it presents several disadvantages according to the application fields. In this study, blockchains performed on application basis were compared. The advantages and disadvantages of this system, which is called the technology of the future, are examined and compared in detail. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: blockchain; consensus; distributed; security